2012
DOI: 10.3892/or.2012.1753
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin acts as an antioxidant and downregulates CYP1A1 and CYP1B1 against DMBA-induced oxidative stress in mice

Abstract: Abstract. We investigated the effects of quercetin on 7,12-dimethylbenz(a)anthracene (DMBA)-induced oxidative stress and the expression of CYP1A1 and CYP1B1 in mice. Quercetin was administered orally to mice at 100 or 250 mg/kg BW for 18 days, after which DMBA (34 mg/kg BW) was administered intragastrically twice. Quercetin showed side effects such as increased aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in DMBA-untreated mice. Also, quercetin induced AST and ALT in DMBA-treated, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The results from this study showed significantly higher CYP1A1 activity in DMBAinduced rats that were not pretreated with KV. This finding agrees with a study which showed higher CYP1A1 activity in rodents administered DMBA (Choi et al, 2012). CYP1A1 activity is comparatively higher in breast cancer cells in contrast with healthy breast epithelial cells (Spink et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results from this study showed significantly higher CYP1A1 activity in DMBAinduced rats that were not pretreated with KV. This finding agrees with a study which showed higher CYP1A1 activity in rodents administered DMBA (Choi et al, 2012). CYP1A1 activity is comparatively higher in breast cancer cells in contrast with healthy breast epithelial cells (Spink et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…CYP1A1 metabolizes various xenobiotics including DMBA and estrogen, resulting in oxidized compounds that contribute to oxidative stress and mammary carcinogenesis (Go et al, 2017). In rodents induced with mammary carcinogenesis using DMBA, increased levels of pro-inflammatory cytokines (Forcados et al, 2020) and elevated levels of oxidative stress markers (Choi et al, 2012) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We found that CYP1B1 was the target of quercetin, which was consistent with the previous reports. Choi et al reported that quercetin acted as an antioxidant and downregulated CYP1B1 against 7,12-dimethylbenz(a)anthracene-induced oxidative stress in mice [41]. Quercetin showed strong and selective inhibition against CYP1B1, which required 2-3 double bonds on the Cring [42].…”
Section: Discussionmentioning
confidence: 99%
“…Corn oil is another vehicle used for the delivery of different drugs including quercetin. 26 In this study, we formulated quercetin in 3 different vehicles, namely, DMSO, ointment base, and corn oil. These 3 formulations of quercetin were comparatively evaluated for the vehicle effects on wound healing potentials of quercetin in rats.…”
Section: Discussionmentioning
confidence: 99%